2015
DOI: 10.12911/22998993/2948
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Utilization as a Renevable Energy Source in Polish Power Industry – Current Status and Perspectives

Abstract: Currently, like in previous years, the main sources of energy for the industry and municipal management are fossil fuels such as hard coal, lignite, crude oil and natural gas. Non-renewable resources of these fuels decrease, what may result in a lack of energy supply. Their exploitation conflicts with the principle of sustainable development and can lead to irreversible geomorphological changes in the environment. The common use of fossil fuels also involves significant dust and gas emissions, including sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Previous studies demonstrated that combustion of biomass emits less SO 2 compared to coal and has zero-balance carbon dioxide emission [27,28]. Furthermore, the ash gained from the combustion of biomass is returned to the soil, where the plants used for thermal process were cultivated and collected, is consistent with the principles of sustainable development [21]. Despite the fact that electric energy in Poland is obtained mainly from coal [17], it has been demonstrated that using biomass from agriculture co-products for energy purposes is fully justified [23].…”
Section: The Role Of Biomass In Energy Production In Polandmentioning
confidence: 56%
See 4 more Smart Citations
“…Previous studies demonstrated that combustion of biomass emits less SO 2 compared to coal and has zero-balance carbon dioxide emission [27,28]. Furthermore, the ash gained from the combustion of biomass is returned to the soil, where the plants used for thermal process were cultivated and collected, is consistent with the principles of sustainable development [21]. Despite the fact that electric energy in Poland is obtained mainly from coal [17], it has been demonstrated that using biomass from agriculture co-products for energy purposes is fully justified [23].…”
Section: The Role Of Biomass In Energy Production In Polandmentioning
confidence: 56%
“…Biomass is one of the oldest as well as the most promising development of RES in Poland, with a great potential to be used for energy purposes [21]. It is mostly related to favourable geographical and climatic conditions for biomass production, wide range of its application, and its large resources [21][22][23].…”
Section: The Role Of Biomass In Energy Production In Polandmentioning
confidence: 99%
See 3 more Smart Citations